Serum Sodium in Acute Stroke and its Clinical Correlation - Sah, Dayanand Prasad; Mahaseth, Adarsha; Sah, Priyanka (Med Phoenix, 2024)
Introduction: Hyponatremia is a frequent electrolyte disturbance in acute stroke, associated with poor clinical outcomes. This study examines the correlation between serum sodium levels and clinical outcomes in acute stroke patients. Materials and Methods: A cross-sectional study of 100 adult stroke patients confirmed by CT/MRI was conducted at a tertiary care hospital. Demographic and clinical data were collected, with stroke severity assessed using the Glasgow Coma Scale (GCS) and Modified Rankin Scale (mRS). Statistical analysis evaluated the association between serum sodium levels and stroke parameters. Results: The cohort included 63% males and 37% females, with a mean age of 64 years. Ischemic strokes (58%) were more common than hemorrhagic strokes (41%), and 1% had mixed findings. Right-sided strokes (55%) slightly exceeded left-sided strokes (45%). Dysnatremia was present in 31%, comprising 28% hyponatremia and 3% hypernatremia. Hyponatremia was significantly associated with hypertension (p = 0.010), lower GCS scores (p < 0.001), and worse mRS outcomes (p = 0.005). No significant correlations were found between sodium levels and stroke type (p = 0.241), laterality (p = 0.244), or diabetes (p = 0.246). Middle circulation strokes were the most prevalent (90%), with no sodium-related differences by territory. Conclusion: Hyponatremia correlates with increased stroke severity and poorer functional outcomes, emphasizing its prognostic value. Its association with hypertension highlights the importance of monitoring sodium levels in hypertensive stroke patients. These findings highlight serum sodium's role in acute stroke management to potentially improve clinical outcomes.